Measuring cognitive fusion through the Cognitive Fusion Questionnaire-7: Measurement invariance across non-clinical and clinical psychological samples - Donati, Maria Anna; Berrocal, Carmen; Bernini, Olivia; Gori, Costanza; Primi, Caterina (PloS one, 2021)
Cognitive fusion (CF) occurs when people are entangled in their private experiences. Rigid patterns of CF are a risk factor for various forms of psychopathology. The most widely used self-report instrument for assessing CF is the Cognitive Fusion Questionnaire–7 (CFQ-7), a unidimensional scale with good reliability and validity. However, its psychometric properties have been studied mainly in non-clinical samples and by applying Classical Test Theory. The goal of this study was to use Item Response Theory to investigate the adequacy of the scale in a non-clinical sample and to test measurement invariance across non-clinical and clinical psychological samples. The non-clinical sample consisted of 258 undergraduate students (68.2% females, Mage = 24.3), while the clinical sample consisted of 105 undergraduate students with psychological distress (60.7% females, Mage = 23.8). The results showed that CFQ-7 assesses a wide range of CF severity among non-clinical subjects and that it is useful to discriminate different levels of CF. Moreover, the results showed the scale was sufficiently informative for a broad range of the trait. The relationships of CFQ-7 scores with theoretically related constructs provided further support to the validity of the scale. The Differential Item Functioning analysis showed that CFQ-7 is invariant across different types of population. Overall, findings in this study provide support for the adequacy of the CFQ-7 both in non-clinical and clinical contexts.